Aging Properties of Polyvinylidenefluoride-Coated Polyesters Used in Tensioned Membrane Structure: Effect of Loading Protocol and Environment - Yingying Zhang; Mingyue Zhang (Advances in Materials Science and Engineering)
This paper presents the degradation behaviors of polyvinylidenefluoride- (PVDF-) coated polyesters used in tensioned membrane structure by artificial accelerated tests, in which the effects of environment factors and loading conditions are studied. Results show that the degradation ratio of main mechanical parameters (tensile strength, tear strength, and elastic modulus) is related to the aging depth of substrate and coating. The degradation of weather resistance can be considered as the accumulation of environment and loads. The ultraviolet radiation and the temperature mainly affect the mechanical properties of yarns, while the preloading before aging tests can change the crimp degrees and decrease the coating thickness. The effect of loads should not be ignored in the weather resistance analysis of PVDF-coated polyesters. A simplified method composed of cyclic tests and stress-relaxation tests is suggested to study the long-term weather resistance of PVDF-coated polyesters. It can provide a theoretical reference for the proposal of resistance partial factor in the design of tensioned membrane structure.